Optical fiber temperature sensor - Chew, Dennis Han Yi (2016)
This project aims to design an appropriate packaging system for microfiber sensor, which features a temperature controller of the sample. This is important to keep temperature influence as minimum as possible, hence, keeping error bar of measurement as low as possible. This is required since the temperature will affect the amount of evanescent field and make the microfiber less efficient. A standard single mode optical fiber is used to fabricate into an optical microfiber by tapering technique. The tapered optical fiber is use as a fiber-optic temperature sensor. The reason for using optical fiber taper is because it has higher sensitivity and the fabrication process is much simpler as compared to Fiber Bragg Grating (FBG) and Long-Period Grating (LPG). In the experiment, optical fiber taper will be used to find out the difference of phase shift when temperature is increased. The current microfiber sensing system does not have a temperature feedback feature, and it takes up an unnecessary amount of time for the samples to equilibrate to surrounding temperature before measurement can be done. Therefore, a temperature feedback system is implemented to eliminate the temperature effect on the microfiber sensor. The temperature feedback feature designed in the experiment uses a PID controller that controls the heating rod to maintain the desired temperature of the water in a confined area, whereby the microfiber is also immersed in the water. From this experiment, it is possible to determine the effect of temperature on the amount of wavelength shift from the microfiber signal. Lastly, the temperature feedback system ensures the surrounding environment temperature will not affect the amount of evanescent field gain by the microfiber.